Poul Thestrup, Dorrit Andersen, Niels Oxenvad: Mod bedre tider Odense 1789-1868. Odense bys historie, bd. 8. (Odense Universitetsforlag, 1986) 499 s. 240,- kr. - Fode, Henrik (Historie/Jyske Samlinger, 1989)
-